Removal of SO2 over Modified Activated Carbon in Fixed Bed Reactor: I, Effect of Metal Oxide Loadings and Acid Treatment - K. Ibraheem, Neran; R. Raouf, Shahrazad; A. Naser, Zainab (Iraqi Journal of Chemical and Petroleum Engineering, 2014)
The removal of SO2 from simulated gas stream (SO2 + air) in a fixed bed reactor using Modified Activated Carbon (MAC) catalysts was investigated. All the experiments were conducted at atmospheric pressure, initial SO2 concentration of 2500 ppm and bed temperature of 90oC. MAC was prepared by loading a series of nickel and copper oxides 1, 3, 5, 7, and 10 wt% on AC. In some of the experimental runs, the original activated carbon was pretreated with two different concentrations of nitric acid 10 and 45 wt%. The results showed that the SO2 removal efficiency, breakthrough time (τ0.05) and sorption capacity increase with increasing metal oxides loadings up to a value of 7 wt% beyond which the desulfurization performance decreases. The pretreatment of the original AC with HNO3 enhanced the removal efficiency of SO2. The copper supported catalysts showed higher flue gas desulfurization activity as compared to the nickel supported catalysts.